THE FINANCIAL PERFORMANCE IN THE INDONESIAN BANKING INDUSTRY REVIEW FROM GOOD CORPORATE GOVERNANCE AND INTELLECTUAL CAPITAL - Sinta Zahrotul Ulya; Elen Puspitasari (Magister Akuntansi, Universitas Atma Jaya Makassar, 2022)
This study aims to determine the effect of Good Corporate Governance and Intellectual Capital on the financial performance of Indonesian banking companies. Good Corporate Governance in terms of Board of Directors, Audit Committee, and Independent Commissioners. Intellectual capital measured by the efficiencies of human capital, structural capital, relational capital and capital employed. The population of this study is all banking companies listed on the Indonesia Stock Exchange for the 2017-2020. The number of samples from using purposive sampling technique obtained were 28 companies with 112 data observations. The major of financial performance proxied by Return on Assets and Capital Adequacy Ratio. This research uses multiple linear analysis method. The results of this study indicate that the Board of Directors and the efficiency of Human Capital, Structural Capital, Relational Capital, and capital employed have a significant positive effect on financial performances. Meanwhile, the Audit Committee and Independent Commissioner have no significant effect on financial performances.